AB0513 Treatment Strategy Targeting Structural Remission in Patients with Early Rheumatoid Arthritis: A Multi-Central, Prospective, Comparative Study Targeting Joint Damage to Zero (Zero-J Study). (9th June 2015) - Tanaka, Y.; Hirata, S.; Amano, K.; Atsumi, T.; Yamamoto, K.; Sumida, T.; Takeuchi, T.; Kohsaka, H.; Mimori, T.; Kawakami, A.; Nishimoto, N.; Tanaka, E.; et al.
Abstract : Background: Rheumatoid arthritis (RA) is a systemic autoimmune disease characterized by inflammation and joint destruction. MTX and biological DMARDs (bDMARDs) have revolutionized treatment of RA and clinical remission and structural remission are now realistic targets. However, we still experience patients with joint destruction by the retardation of appropriate treatments. Thereby, treatment strategy targeting structural remission in patients with early RA is prerequisite. Objectives: The ZERO-J study (UMIN000001281) was undertaken to clarify strategic treatments that successfully reduce and stop joint destruction in ERA. Methods: 162 patients who meet all of the following criteria were registered from 10: diagnosed with the 2010 ACR/EULAR criteria, MTX-naïve, ACPA-positive, disease duration <2Y (mean=7.4M) and bone erosion in hands and feet <3. The treatment was initialized with MTX 6-8 mg/w and the dose was increased by the maximum in each patient within 3M. At M3, if patients fulfilled DAS28(ESR) <3.2 and no new bone erosion, MTX was continued for further 1Y as high responders (HR group). If not, they were treated with the combination of MTX and TNF-inhibitors (TNFi group) or MTX and DMARDs (DMARDs group) for further 1Y. The primary end points at M15 were the mean changes from baseline in the Sharp-van der Heijde score (SHS). Results: DAS28 (from 4.8 to 3.7), SDAI (20.4 to 12.2) and SHS (5.7 to 6.0) changed by MTX for 3 months (means 12.0 mg/w) and 151 patients were divided to 3 groups based on investigator and/or patient decision; TNFi-group (N=35, DAS28=5.6, SDAI=28.6 at M3), DMARDs-group (N=29, DAS28=4.0, SDAI=12.2) and HR-group (N=87, DAS28=2.8, SDAI=5.2). Thus, 58% of them were high responders to 3M-treatment with MTX. At M15, DAS28 (TNFi=2.7, DMARDs=2.9, HR=2.7) and SDAI (TNFi=5.5, DMARDs=5.9, HR=5.3) were comparable among groups (LOCF). However, changes in SHS from BL to M15 were significantly higher in TNFi group (1.0) than DMARDs group (0.7) and HR group (0.5), structural remission rate was observed significantly lower in a TNFi group (65%) than those in DMARDs group (74%) and HR-group (87%), and clinical relevant radiographic progression was observed in 6% of TNFi, 5% of DMARDs and 3% of HR-group. Conclusions: About 60% of early RA patients were high responders to MTX within 3 months and structural as well as clinical remission was sustained for further 12 months in the majority of the HR group, indicating that bDMARDs may not be required to these MTX-HR patients. In contrast, less proportion of patient revealed structural remission in TNFi group, about 20% of ERA patients, 3-months retardation of intervention with bDMARDs resulted in progress in joint damages in the population. These results indicated that substantial proportions of patients have benefited from induction with MTX and bDMARDs to target joint damage to ZERO. Disclosure of Interest: Y. Tanaka Grant/research support from: Mitsubishi-Tanabe, Chugai, MSD, Astellas, Novartis, Speakers bureau: Abbvie, Chugai, Astellas, Takeda, Santen, Mitsubishi-Tanabe, Pfizer, Janssen, Eisai, Daiichi-Sankyo, UCB, GlaxoSmithKline, Bristol-Myers, S. Hirata: None declared, K. Amano Grant/research support from: Astellas, Chugai, Pfizer, Tanabe-Mitsubishi, Paid instructor for: Chugai, Tanabe-Mitsubishi, Pfizer, Santen, Speakers bureau: AbbVie, Actellion, Astellas, Bristol-Myers-Squibb, Chugai, Diichi-Sankyo, Eisai, Pfizer, Tanabe-Mitsubishi, T. Atsumi Grant/research support from: Chugai Pharmaceutical Co. Ltd., Eisai Co. Ltd., Bristol-Myers Squibb Co., Astellas Pharma Inc., Daiichi Sankyo Co. Ltd., Mitsubishi Tanabe Pharma Co, Speakers bureau: Astellas Pharma Inc., Mitsubishi Tanabe Pharma Co., K. Yamamoto Grant/research support from: Astellas, AbbVie, Takeda, TEIJIN, Pfizer, Bristol-Myers, DAIICHI SANKYO, Mitsubishi-Tanabe, Chugai, Janssen, Eisai, Speakers bureau: Astellas, abbvie, Eisai, Pfizer, Bristol-Myers, Janssen, UCB, Asahi Kasei, Santen, ONO, Taisho Toyama, DAIICHI SANKYO, AstraZeneca, Chugai, TEIJIN PHARMA, Mitsubishi-Tanabe, Boehringer Ingelheim, Nippon Kayaku, Takeda, T. Sumida: None declared, T. Takeuchi Grant/research support from: Astellas Pharma, Bristol–Myers K.K., Chugai Pharmaceutical Co, Ltd., Daiichi Sankyo Co., Ltd., Eisai Co., Ltd., Mitsubishi Tanabe Pharma Co., Pfizer Japan Inc., Santen Pharmaceutical Co., Ltd., Takeda Pharmaceutical Co., Ltd., Teijin Pharma Ltd., AbbVie GK, Asahikasei Pharma Corp., and Taisho Toyama Pharmaceutical Co., Ltd., SymBio Pharmaceuticals Ltd., Consultant for: Astra Zeneca K.K., Eli Lilly Japan K.K., Novartis Pharma K.K., Mitsubishi Tanabe Pharma Co., and Asahi Kasei Medical K.K., abbivie GK, Daiichi Sankyo Co., Ltd., Bristol–Myers K.K., Nipponkayaku Co.Ltd., Paid instructor for: Mitsubishi Tanabe Pharma Co., Eisai Co., Ltd., Abbivie GK, Speakers bureau: AbbVie GK., Bristol–Myers K.K., Chugai Pharmaceutical Co, . Ltd., Eisai Co., Ltd., Janssen Pharmaceutical K.K., Mitsubishi Tanabe Pharma Co., Pfizer Japan Inc., and Takeda Pharmaceutical Co., Ltd., Astellas Pharma, and Diaichi Sankyo Co., Ltd., Celtrion, Nipponkayaku Co.Ltd, H. Kohsaka Grant/research support from: Mitsubishi Tanabe Pharma Corporation Takeda Pharmaceutical Company Limited Bristol-Myers Squibb Eisai Co., Ltd. Teijin Pharma Limited Pfizer Inc. Actelion Pharmaceuticals Japan Ltd. Santen Pharmaceutical Co, .Ltd. Ono Pharmaceutical Co., Ltd. Daiichi Sankyo Company., Limited. Nippon Kayaku Co., Ltd. Abbie Inc. AstraZeneca plc., Paid instructor for: Teijin Pharma Limited Chugai Pharmaceutical Co., LTD., Speakers bureau: Mitsubishi Tanabe Pharma Corporation Takeda Pharmacentical Company Limite Abbie Inc. Ono Pharmaceutical Co., LTD. UCB Japan Co. Ltd. Astellas Pharma Inc. Chugai Pharmaceutical Co., LTD. Japan Blood Products Organization Asahi Kasei Corporation, T. Mimori: None declared, A. Kawakami Grant/research support from: Abbvie GK, Eisai Co., Mitsubishi Tanabe Pharma Co., Pfizer Japan, Janssen Pharmaceutical K. K., Takeda Pharmaceutical Company Astellas Pharma Inc., Speakers bureau: Abbvie GK, Eisai Co., Mitsubishi Tanabe Pharma Co., Pfizer Japan, Janssen Pharmaceutical K. K., Takeda Pharmaceutical Company Astellas Pharma Inc., N. Nishimoto: None declared, E. Tanaka: None declared, Y. Kaneko Consultant for: Abbvie, Paid instructor for: Eisai Pharmaceutical, Chugai Pharmaceutical, Astellas Pharmaceutical, Mitsubishi Tanabe Pharma Corporation, Pfizer, Speakers bureau: Abbvie, Eisai Pharmaceutical, Chugai Pharmaceutical, Bristol Myers Squibb, Astellas Pharmaceutical, Mitsubishi Tanabe Pharma Corporation, Pfizer, Janssen, UCB, H. Yasuoka Consultant for: AbbVie Inc, S. Fukuyo: None declared, K. Saito: None declared